ARTYSTA WOBEC ZBIOROWEGO DOŚWIADCZENIA ZMIERZCHU. PRZECIW DUCHOWI CZASU. ZYGMUNT MYCIELSKI W LISTACH DO NADII BOULANGER Z LAT 1939–1940 - Klubiński, Michał (Colloquia Litteraria, 2025)
The article attempts to analyse selected letters by Zygmunt Mycielski to his Parisian master, the most outstanding twentieth-century composition teacher, Nadia Boulanger, from 1939–1940. Mycielski’s view on the twilight of European civilisation—in the face of the war against German totalitarianism—is filtered through questions about Mycielski’s altering paradigm as an artist and the relevance of the classical attitude. Analysis is also proposed of the concept of ‘twilight of the divine cycle of humanity’, borrowed by Mycielski from Karol Hubert Rostworowski, which, in the light of the former’s views on civilisation presented in his diaries and references to the ideas of Jacques Maritain, appears to be a redefinition of the artist’s perception of collective subjectivity